Single-cell transcriptomic and m6A methylation analyses reveal platelet-mediated immune regulatory mechanisms in sepsis - Qian, Weiwei; Liu, Yuanyuan; Zhao, Xinyang; Dong, Yuxin; Zhou, Jian; Shou, Songtao (Frontiers in Immunology, 2025)
ObjectiveSepsis is a systemic inflammatory response syndrome triggered by infection, characterized by high clinical heterogeneity and complex immunopathological mechanisms. Immune dysregulation plays a central role in its progression. This study aims to investigate the compositional changes of immune cells, characteristics of intercellular communication, and potential regulatory mechanisms of N⁶-methyladenosine (m6A) modification in sepsis, with a particular focus on the functional remodeling of platelets.MethodsThis study integrated single-cell RNA sequencing data (GSE167363 dataset) from sepsis patients with m6A methylation sequencing data of peripheral blood mononuclear cells (PBMCs). Through systematic analysis, we compared the differences in immune cell composition, developmental trajectories, intercellular communication, and m6A modifications among healthy controls, survivors, and non-survivors, and further screened for key m6A-regulated target genes.ResultsThe analysis revealed that platelets gradually accumulated during the progression of sepsis, while B cells, T cells, and regulatory T cells (Tregs) exhibited a trend toward platelet-like phenotypic remodeling. Cell–cell communication analysis showed a marked decline in communication strength among immune cells as the disease worsened, particularly a significant weakening of the APP–CD74 signaling pathway between platelets and B cells, indicating impaired immune network synergy. m⁶A methylation sequencing revealed distinct remodeling of m⁶A peaks and dysregulation of related regulatory factors in non-survivors. Further integrative analysis identified RPA1 as a key m⁶A-regulated target gene, whose expression was closely associated with APP and co-regulated by multiple m6A-modifying factors.ConclusionThis study reveals disruptions in immune cell interactions and an m6A-dependent mechanism of platelet functional remodeling during sepsis progression. The identification of the key target gene RPA1 offers new insights into the immunopathological mechanisms of sepsis and lays a theoretical foundation for future precision interventions and therapeutic strategies.